Content Analysis Of Books In Learning Arabic For Primary School On The Basis Of The Common European Framework Of Reference (CEFR)/ تحليل محتوى الكتب في تعليم للغة العربية للإبتدائية على أساس الإطار المرجعي الأوروبي المشترك ( CEFR) - Lilis Suaibah; Imam Asrori; Abdul Wahab Rosyidi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Textbooks have an essential role in the educational process. They are the essential means necessary to achieve the objectives of the educational curriculum and their active role in the success of the educational process. In addition, textbooks contain materials for educational objectives and attention to the level of thinking, knowledge, skills, and affection that students must learn in order to obtain the relevant basic competency. A good textbook should have standards that conform to the standard. Indonesia did not have a specific standard for teaching Arabic or competencies in Arabic. The reference frameworks in the world have varied in this field, including the European Common Reference Framework. This research aims to analyze the content of books teaching Arabic for first, second, and third graders based on the Common European Framework of Reference (CEFR). The use of this research is qualitative research, and the method of data collection uses the library research method using a tool from the book of highlights, while data analysis uses the analytical techniques of the content and the standard of the universality of the typical European frame of reference and the results of the research is the analysis of the contents based on the standard of the universality of the typical European frame of reference which are six contents (7,69%) fit at level A1 pra (not matched with level efficiency), 66 contents (84.62%) fit at level A1 (beginner), and 6 contents (7.69%) fit at level A2 (Elementary).